Revealing the specificities of the interaction between ants and plants bearing extrafloral nectaries: direct impacts on plants, herbivores, ants and pollinators - Soares, Eduardo Calixto (2019)
The ant-plant relationship mediated by extrafloral nectaries (EFNs) is a classic and well documented model of biotic plant defense, in which plants offer extrafloral nectar, a liquid food resource, and in return ants defend plants by preying on or repelling herbivores. On the other hand, the ant aggressive behavior might be detrimental to plants, since they can end up repelling or preying on pollinators and consequently influencing the plant\'s reproductive success. In this perspective, we evaluated the specificities of ant-plant interaction and the impacts of ants on herbivores and pollinators in plants bearing EFNs. The study was conducted from September 2015 to July 2018, in a reserve of cerrado stricto sensu, located in Uberlândia, Brazil. In Chapter 1, we presented a review of scientific texts of the last 30 years on the history of the art of protective mutualism between ants and plants with EFNs and the perspectives of this topic. In Chapter 2, we demonstrated the short- and long-term benefits of extrafloral nectar and artificial food source on ant colony fitness (number and weight of individuals) and survival, in which the presence of extrafloral nectar and food sources rich in carbohydrates and proteins positively influence the growth and survival of the colony. In Chapter 3, we showed that the activity of EFNs influences the ant-herbivore relationship leading to patterns of seasonality and synchronism of herbivore and ant populations, with different herbivore predation rates, and impacts on plant fitness. And finally, in Chapter 4, we observed that the protective mutualism between ants and EFN-bearing plants may negatively influence plant fitness via deterring visitation by pollinators. We showed that extrafloral nectar is a key factor in the regulation and structuring of ecological interactions, directly influencing the growth and survival of ant colonies, as well as in the interaction of ants with herbivores and pollinators in plants bearing extrafloral nectars. In this perspective, we should study each ecological system in detail, knowing all interacting beings, as well as their respective natural histories, to understand the patterns of interaction and the structuring of food chains, which directly influence the natural ecosystems dynamic.